EFEKTIVITAS MODEL PEMBELAJARAN INKUIRI TERBIMBING BERBASIS MULTIREPRESENTASI PADA MATERI ELEKTROLIT DAN NON ELEKTROLIT DALAM MENINGKATKAN KETERAMPILAN MENGOMUNIKASIKAN - Putri Friskwila Simanjuntak; M. Setyarini; Ni Putu Rahma Agustina (STKIP Subang, 2026)
This study aimed to examine the effectiveness of a guided inquiry learning model based on multiple representations in improving students' communication skills on the topic of electrolyte and non-electrolyte solutions. The population consisted of all Grade X students at SMA Gajah Mada Bandar Lampung during the 2025/2026 academic year, comprising six classes X.1–X.6. The sample was selected using purposive sampling, resulting in Class X.2 as the experimental group and Class X.6 as the control group. This study employed a quasi-experimental method with a nonequivalent pretest–posttest control group design. The research instruments consisted of pretest and posttest essay tests to assess students' communication skills and student activity observation sheets. The data were analyzed using the normalized gain (N-gain), followed by hypothesis testing with an independent-samples t-test after the assumptions of normality and homogeneity had been satisfied to determine the difference in the improvement of communication skills between the two groups. The results showed that the experimental class achieved a mean N-gain score of 0.71, which was categorized as high, whereas the control class obtained a mean N-gain score of 0.58, which was categorized as medium. The hypothesis test indicated that the mean N-gain score of the experimental class was significantly higher than that of the control class. These findings demonstrate that the guided inquiry learning model based on multiple representations is effective in improving students' communication skills on the topic of electrolyte and non-electrolyte solutions.